Pengaruh Gaya Kepemimpinan Kepala Desa Terhadap Partisipasi Masyarakat Dalam Pembangunan Desa Pattirolokka Kecamatan Keera Kabupaten Wajo - Dedi Irwanda; Burhanuddin Burhanuddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The presence of a good government with leaders legally chosen by the people in government organizations in particular will require a sharp appreciation of human behavior if they have to provide encouragement to the people they lead. A leader in an organization, whether a leader in a government organization in particular, will need effective work in order to influence the quality of work of officials in carrying out their duties, so the most important thing is that organizational dynamics can run well if leadership functions can be implemented. The main goal of a leader is to know the influences and be able to encourage the people he leads to act to achieve predetermined goals. Someone who acts as an employee expects encouragement and support in an effort to improve their performance, therefore these two sides need to have a strong will in achieving organizational goals.